Quality of Educational Services as a Determinant of Regional Economy Development - Hermaniuk, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
Contemporary socio-economic environment puts higher demands of university graduates. In addition, common access to education at the university level, a large number of entities competing for acquisition candidates and the growing expectations of current and future students make it becomes increasingly important to offer educational services at the high level of quality. To meet these circumstances, universities are reaching for professional marketing and quality assurance tools. In order to match the offer to the customer’s requirements, it is necessary to carry out a systematic measurement of expectations and the extent of their current implementation. Powerful tool, useful in the diagnosis of this condition is the SERVQUAL method, the main idea of which focuses on comparing the customer’s expectations with services received. As a result of this comparison, it becomes possible to identify major gaps and disparities in relation to the expected values and received by the customer. The article presents the results of the research on the satisfaction level of students of the Faculty of Economics, University of Rzeszow carried out using the method of SERVQUAL.

Współczesne otoczenie społeczno-ekonomiczne stawia coraz wyższe wymagania absolwentom wyższych uczelni. Dodatkowo powszechny dostęp do edukacji na poziomie akademickim, duża liczba podmiotów rywalizujących o pozyskanie kandydatów na studia oraz rosnące oczekiwania obecnych i przyszłych studentów sprawiają, że coraz większego znaczenia nabiera oferowanie odpowiedniej jakości usług edukacyjnych. Wychodząc naprzeciw tym zjawiskom uczelnie sięgają po coraz bardziej profesjonalne narzędzia marketingu i zapewnienia jakości. W celu dopasowania oferty do wymagań klienta niezbędne jest prowadzenie systematycznego pomiaru oczekiwań oraz stopnia ich bieżącej realizacji. Skutecznym narzędziem, pomocnym w rozpoznaniu tego stanu, jest metoda SERVQUAL, której główna idea sprowadza się do porównania oczekiwań klienta z percepcją usługi otrzymanej. Na skutek tego porównania możliwe staje się rozpoznanie najważniejszych luk i dysproporcji w odniesieniu do wartości oczekiwanych i otrzymywanych przez klienta. W artykule przedstawiono wyniki badań poziomu satysfakcji studentów Wydziału Ekonomii Uniwersytetu Rzeszowskiego przeprowadzonych z zastosowaniem metody SERVQUAL.